HEALTH-SEEKING BEHAVIOR OF TUBERCULOSIS PATIENTS IN BHUBANESWAR, ODISHA, INDIA - Saumyasree Pradhan; Barsha Rani Mohapatra; Jena, Monika; Kund, Nitushree; Senapathy, Nihar Nalini; Mohapatra, Amarendra (Universitas Airlangga, 2024)
Introduction: Tuberculosis (TB) is an infectious disease with a significant global impact, without treatment, the death rate from TB disease is high (about 50%) Aims: The study conducted in Bhubaneswar aimed to assess tuberculosis disease burden, health-seeking behaviour, and to find the gap of non-compliance in the medicine. Methods: A cross-sectional survey was conducted among TB patients in UPHCs Sahid Nagar and IRC Village of Bhubaneswar, Odisha. All new adult smear positive PTB patients diagnosed and treated in any of the government health facilities within these block PHC areas between 1 July to 31 September 2023, were identified, traced and interviewed using a pre-tested, semi-structured, coded interview. Results: On drug compliance, it was found that patients in the age group above 50 were compliant with treatment 86.2% by taking medicine regularly then their comparison age groups. Education beyond high school positively impacted compliance (100%), as did dependency status (88.9%). Alcohol addiction was prevalent among 47% of male patients and 11.4% of females, while smoking rates were 33.3% among males and 4.5% among females. Dependents consumed less alcohol (17.5%) than employed (55.8%), and younger patients smoked more (36.4%) than older age groups (31.7%). Non-educated patients smoked more (32.5%) than educated counterparts. Self-employed individuals smoked more (75%) than employed (37.2%). Chi square test highlighted that employment correlated with higher alcohol consumption (55.8%), impacting drug compliance negatively. Conclusion: Elderly patients, females, and those educated beyond high school exhibited better treatment completion rates. The study recommends targeted educational interventions to enhance TB treatment.